Evaluation of Psychological Skills and Effect of an Educational Curriculum with a Model to Accelerate Thinking in the Arbitrary Performance of Students with Handball - ALaa Ihsan Ali alrikabi1 , Wissam Salah Abdel-Hassan1 , Abbas Abdulalhamza Kadhim3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The aim of the research is to identify the effect of the educational curriculum prepared with the model toaccelerate thinking in the arbitration performance of students with handball and the extent of their response.Experimental approach used to design (two equal groups) with pre and post tests to suit the nature of theresearch and its problem, and the researcher identified the research community with the fourth stage studentsin the College of Physical Education and Sports Science / Dhi Qar University, who are (90) students for theacademic year (2019/2020) distributed On two divisions (A & B), where the division (A) was identified asa sample for research, (30) students were selected, including a sample for research and (10) students for asurvey sample Also in the simple random method, then the researcher designed a form for evaluating thearbitration performance of students with handball and was presented to the experts and specialists, whonumber (15) expert and specialist in handball game in order to determine the validity of the form paragraphs,and appropriate statistical treatments were used to reach the results, then they were Presentation, analysisand discussion of results.